Penentuan Arah Kiblat Menggunakan Rubu' Mujayyab - Muhammad Ansori; sapri ali (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2022)
The problem is the variety of tools used in determining the direction of the Qibla, both classical and modern, for example using a special stick, Global Qibla Rashdul, local Qibla rashdul, theodolite, miqyas, rubu 'mujayyab, theodolite, GPS (Global Positioning System) and others. So that the figures of astronomy sometimes differ in terms of determining the direction of the Qibla. The more sophisticated these tools, the higher the azimuth data accuracy will be. With the development of time found a tool that shows the direction of the wind called a compass. The compass is made of a magnetic needle which consists of two poles, namely the north and south poles and is equipped with a protractor, so that this compass pointing tool is very useful for Muslims and can determine the Qibla direction. Departing from the description above, the author is interested in discussing one of the classic tools, namely the rubu 'mujayyab which has been used for years by falaq experts among Islamic boarding schools, this of course has weaknesses and strengths. In this study, the issue discussed is how is the accuracy level of determining the Qibla direction using the rubu 'mujayyab? What are the advantages and disadvantages of determining the Qibla direction using rubu 'mujayyab? The type of research used by this author is classified as qualitative, which aims to better understand the rubu mujayyad where the primary data is data obtained directly from observations, the book of durussul falakiyyah and secondary data are all documents in the form of books, writings, journals, papers related to the object study. The findings from this research are that when the practice of measuring the Qibla is not the same, there is a difference of about 0˚ 8′ 52.42ʺ which if made in meters from the east to west line distance which is both 9 meters produces a difference of about 0.03 meters . According to the author, this is still within reasonable limits or allowed deviation categories. maybe this is due in part to the advantages and disadvantages of each of the two tools. The advantages contained in the rubu 'mujayyab is more accurate because it relies on direct sunlight. While the lack of rubu 'mujayyab, the data on rubu' mujayyab is limited to degree data, so it requires accuracy from people who calculate, only astronomers can do it, cannot be used in cloudy conditions and so on.